PERFORMANCE PROMISING LINES OF MAIZE ON DRY ACID SOIL IN DISTRICT OF TALAWI, SAWAHLUNTO - Sumilah Sumilah; Atman Atman (Widyariset, 2013)
Maize development is potential in West Sumatera. Maize is strategic commodity, because related to subsector development (feed) and other sector (food and feed industry). The aim of this research was to obtain maize promising lines capable to well adapt in dry acid soil, with pH <5. Research was conducted in farmer cultivation of district of Talawi, Sawahlunto, begin in September to December 2010 at dry acid soil (pH 4,57), using 12 promising lines from Balit Sereal Maros such as GH-1, GH-2, GH-3, GH-4, GH-5, GH-6, GH-7, GH-8, GH-9, GH-10, GH-11, GH-12, and one existing variety as control. The experimental design was a Randomized Completely Block Design (RCBD) with three replications. Land processed perfectly of the size map each 4x6 m. Distance plant 80x15 cm. The packages of fertilizers for maize are 300 kg urea+150 kg SP-36+50 kg KCl per hectare. The observation of the studies were plant growth yield component and yield. The result obtained two maize promising lines (GH-1 and GH-3) capable to produce dry pods yield approximately 4,5 tons/ha and 4,2 tons/ha at dry acid dry soil in Sawahlunto (pH<5).